Multimedia literacy in preschool and primary education - Mikelić Preradović, Nives (Array, 2014)
In this paper, we summarize the necessary elements of multimedia literacy education, its key stakeholders and emphasize its role in the early years of life. We also discuss approaches, similarities, differences, advantages and issues of introducing multimedia literacy education in preschools and primary schools in different countries of the world. Finally, we present results of the empirical research on the sample of 6th graders in order to determine the use of ICT and the level of information and multimedia literacy of school children in Croatia.